The superiority of economists - Marion Fourcade; Etienne Ollion; Yann Algan (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2014)
In this essay, we investigate the dominant position of economics within the network of the social sciences in the United States. We begin by documenting the relative insularity of economics, using bibliometric data. Next we analyze the tight management of the field from the top down, which gives economics its characteristic hierarchical structure. Economists also distinguish themselves from other social scientists through their much better material situation (many teach in business schools, have external consulting activities), their more individualist worldviews, and in the confidence they have in their discipline's ability to fix the world's problems. Taken together, these traits constitute what we call the superiority of economists, where economists' objective supremacy is intimately linked with their subjective sense of authority and entitlement. While this superiority has certainly fueled economists' practical involvement and their considerable influence over the economy, it has also exposed them more to conflicts of interests, political critique, even derision.
Keywords: 330